Clean and Healthy Living Behavior for the Prevention of Dengue Hemorrhagic Fever in the Urban Community: A Descriptive Cross-Sectional Study - Sevira Gebby Pricillia; Reliani Reliani; Chlara Yunita Prabawati; Mundakir Mundakir (Indonesian Academia Health Sciences Journal, 2026)
Background: Household environmental management and sustained preventive behavior remain central to dengue control, particularly in densely populated urban settings. Objective: To describe community knowledge, attitudes, and practices related to Clean and Healthy Living Behavior for dengue prevention in the Wonokusumo Public Health Center catchment area, Surabaya. Methods: A descriptive cross-sectional study was conducted from 7 to 13 August 2023 among 167 household representatives aged 26–70 years in RW 10, Wonokusumo. Participants were recruited using purposive sampling. Data were collected using a structured questionnaire adapted from established dengue knowledge, health-belief, and prevention-practice instruments. Knowledge, attitude, and practice were summarized using frequencies and percentages. Results: Most respondents had good knowledge (127/167; 76.0%) and a positive attitude toward dengue prevention (135/167; 80.8%). However, more than half had poor preventive practices (87/167; 52.0%); only 55 respondents (33.0%) were categorized as having good practices. Respondents were predominantly male (62.2%), aged 37–47 years (38.0%), educated to senior high-school level (45.0%), and married (82.0%). Conclusion: The community demonstrated a clear knowledge–practice gap: favorable knowledge and attitudes had not consistently translated into routine household dengue prevention. Community nursing programs should move beyond information delivery toward repeated household monitoring, practical demonstrations, family participation, and coordinated action with local health volunteers and community leaders.